Covid 19 y su impacto económico y turístico del cantón Quevedo, Provincia de Los Ríos - año 2022 - Chévez Manzano, Paca Teresa (2022)
The theme of Covid-19 was chosen in relation to the tourist and economic impact of Quevedo with the aim of analyzing both the positive and negative effects on the country's economy and at the local level. As is public knowledge, the health emergency brought with it alternatives to avoid contagion, such as: social distancing, the permanent use of the mask and, in turn, confinement in between 3 and 6 months, this affecting casualties decreasing in all sectors that contribute to the economy, being its tourism, were sufficient because some recreational spaces remained closed to the public. The methodology applied is of the type, Analytical - Synthetic, Historical - Comparative, Qualitative - Quantitative and, Bibliographic, applying a survey of the population of the Canton Quevedo for data collection, demonstrating that tourism in the canton has always been deficient (59.70 % of those surveyed), due to the lack of support from the Municipal Government and the high crime rate, which substantially affects tourists and businesses in general.